Geohazards: Risk Assessment, Mitigation and Prevention (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint aims to provide a common forum to share knowledge about the growing threat of geohazards such as landslides, earthquakes, floods, tsunamis, coastal changes, and drought, among many others, due to the expanding size of cities and urban areas, the critical use of agricultural lands, the increased use of infrastructure, and the effects of climate change.A total of thirty-one papers (twenty-eight research papers, one review paper, and one technical note) on different topics like coastal changes, landslides, earthquakes, and others are presented in this reprint. The published works have been carried out in different parts of the world, such as Spain, Portugal, France, Italy, Hungary, China, South Korea, India, Malaysia, Algeria, Canada, or Mexico.